Genome-wide identification and comprehensive analyses of NAC transcription factor gene family and expression analysis under Fusarium kyushuense and drought stress conditions in Passiflora edulis - Yang, Qiang; Li, Binqi; Rizwan, Hafiz Muhammad; Sun, Kaiwei; Zeng, Jiajing; Shi, Meng; Guo, Tianxin; Chen, Faxing (Frontiers in Plant Science, 2022)
The NAC gene family is one of the largest plant transcription factors (TFs) families and plays important roles in plant growth, development, metabolism, and biotic and abiotic stresses. However, NAC gene family has not been reported in passion fruit (Passiflora edulis). In this study, a total of 105 NAC genes were identified in the passion fruit genome and were unevenly distributed across all nine-passion fruit chromomere, with a maximum of 48 PeNAC genes on chromosome one. The physicochemical features of all 105 PeNAC genes varied including 120 to 3,052 amino acids, 3 to 8 conserved motifs, and 1 to 3 introns. The PeNAC genes were named (PeNAC001-PeNAC105) according to their chromosomal locations and phylogenetically grouped into 15 clades (NAC-a to NAC-o). Most PeNAC proteins were predicted to be localized in the nucleus. The cis-element analysis indicated the possible roles of PeNAC genes in plant growth, development, light, hormones, and stress responsiveness. Moreover, the PeNAC gene duplications including tandem (11 gene pairs) and segmental (12 gene pairs) were identified and subjected to purifying selection. All PeNAC proteins exhibited similar 3D structures, and a protein-protein interaction network analysis with known Arabidopsis proteins was predicted. Furthermore, 17 putative ped-miRNAs were identified to target 25 PeNAC genes. Potential TFs including ERF, BBR-BPC, Dof and bZIP were identified in promoter region of all 105 PeNAC genes and visualized in a TF regulatory network. GO and KEGG annotation analysis exposed that PeNAC genes were related to different biological, molecular, and cellular terms. The qRT-PCR expression analysis discovered that most of the PeNAC genes including PeNAC001, PeNAC003, PeNAC008, PeNAC028, PeNAC033, PeNAC058, PeNAC063, and PeNAC077 were significantly upregulated under Fusarium kyushuense and drought stress conditions compared to controls. In conclusion, these findings lay the foundation for further functional studies of PeNAC genes to facilitate the genetic improvement of plants to stress resistance.